KAJIAN HUKUM DAN KEBENARAN - Hutabarat, Dany Try Hutama; Rosdiana, Rosdiana; Sitorus, Dinda Mayarni; Yolanda, Betrik; Sajali, Eka; Aisyah, Nur; Panjaitan, Annisa Octaviani; Abimanyu, Aditya P.; Siregar, Sahmul; Denisa, Denisa; Adlina, Desri; Siregar, Fani Ustazah; Ramadhani, M. Risky (Nusantara Hasana Journal, 2022)
To examine a legal truth from a philosophical point of view, one must first understand the meaning of the law itself. Talking about the law in general, namely the whole collection of rules or rules in a common life, in another sense the whole rules of behavior that apply in a common life, which can be enforced with a sanction. There are several theories of truth, namely the theory of coherence or consistency, the theory of correspondence truth, the theory of pragmatism of truth, the theory of truth based on meaning, the theory of syntactic truth, the theory of non-discretionary truth, and the theory of logical truth. A person's belief in the truth of the law depends on the theory he adheres.